PENINGKATAN HASIL BELAJAR MENULIS TEKS ANEKDOT MELALUI PENERAPAN STRATEGI GENIUS LEARNING SISWA KELAS X JASA BOGA 1 SMK NEGERI 2 BONDOWOSO: SMK NEGERI 2 BONDOWOSO - SOEMINIWATI SOEMINIWATI (Dewan Pendidikan Bondowoso, 2021)
The purpose of this research is to be able to improve the anecdotal text writing skills of students of class X Jasa Catering 1 SMK Negeri Bondowoso in the odd semester of the 2018/2019 academic year by implementing a genius learning strategy. This type of research is classroom action research because this research was conducted to solve problems in class. which is carried out in two cycles every cycle of two meetings. The research was carried out in class X Catering Services 1 at SMK Negeri 2 Bondowoso in the odd semester of the 2018/2019 academic year. Data collection techniques were carried out through observation, documentation, learning outcome tests which were analyzed through qualitative descriptive analysis techniques. From the results of the research carried out, it can be concluded that the application of the genius learning strategy can improve the anecdotal text writing skills of class X Catering Services 1 students of SMK Negeri 2 Bondowoso in the odd semester of the 2018/2019 academic year.